Hubungan antara Kualitas Layanan dan Kepuasan Pelanggan: Studi Kasus pada Pelanggan PT Zhisheng Pacific Trading (Mixue Indonesia) - Mintawati, Hesri; Desianti, Lisa Chandrasari; P., Meisya Eka Putri; Firdaus, Rifka Salsabila; Herawati, Dea Ariana (JUDICIOUS, 2024)
Utilizing a qualitative method, this research investigates the customer satisfaction of PT Zhisheng Pacific Trading (Mixue Indonesia). The aim of this study is to gain an understanding of customer’s perceptions regarding the quality of service they receive and to what extent this influences their satisfaction. The research sample consist of 10 clients selected purposively. Data were collected through interviews conducted with the assistance of structured question guides. The data analysis does not involve coding and thematic techniques, but solely encompasses a qualitative assessment of customer responses. The research findings indicate a significant correlation between how customers perceive the services and their level of satisfaction. These results enable PT Zhisheng Pacific Trading to enhance their services to better satisfy their customers.